ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TERJADINYA SELISIH TRANSAKSI PADA TELLER DI BANK BRI KCP TILAMUTA - Wiwin Koni; Adelia Priskawati Puloli (Department of Islamic Banking, Faculty of Islamic Economics and Business, IAIN Sultan Amai Gorontalo, 2022)
This study aims to identify the factors that influence the occurrence of differences in tellers. Then the identification results are used to determine steps that can be taken to anticipate teller transaction errors.This type of research uses qualitative methods, the research approach used in this research is phenomenology. Sources of data in this study are secondary data obtained from interviews with managers and employees at Bank BRI KCP Tilamuta and documentation as well as those sourced from library research in the form of reading books and other sources relevant to this research.This research produces the following findings: First, human and technical factors, human factors occur because of the teller's inaccuracy in inputting data. The technical factor occurs because of a system or network error that occurs in the bank. The two teller responsibilities for errors in carrying out orders have two settlement processes: (1) transferring funds to fellow banks by means of Error Corrections (2) Matching the transfer slip written by the customer, confirming the customer there was an input error, blinding the facsimile note regarding blocking transfers and making RTGS/LLG correction with proper data.